„Wielki wstrząs” – nowe media a kapitał społeczny – pomnażanie czy drenaż? Konieczność wzmacniania merytorycznej i personalistycznej edukacji medialnej dla budowania kapitału społecznego - Miąso , Janusz (Studia Edukacyjne, 2019)
Many eminent experts emphasize the unprecedented scale of current social transformations, which is why such terms as „Great shock” – Fukuyama, „Future shock” – Toffler, „Endangered humanity, anthropological regression” – Szmyd appear. Zbyszko Melosik emphasizes the huge scale of culture transformation, in virtually every dimension of individual and social life. The dynamics of change, however, is primarily new media, which Marshall McLuhan made the force that makes nothing remain unchanged. At the same time, however, man remains a being in great need of genuine closeness, warmth, kindness, all good things and what we call social capital. That is why, however, care for social capital is so important in the climate of great shock, mediation and a huge scale of transformation. Personalist media pedagogy is a concern for man – a person in the space of new media, so that the media can multiply the priceless real social capital.